Synthesis, Characterization, Photoluminescence Emission and Antibacterial Properties of Some Schiff Base Derivatives of Substituted Salicylaldehyde - V. B. , Nagaveni; G.L., Dr. ARUNA; K.M., Dr. Mahadevan (Asian Journal of Chemistry, 2023)
Schiff bases such as 4-[(2-hydroxyphenyl) methylidene]amino benzoic acid analogues (SB1-SB3) have been produced by the condensation of mole equivalent of 4-amino benzoic acid and various substituted salicylaldehyde. It has given good yield. The synthesized compounds (SB1-SB3) were analyzed by FT-IR, 1H-NMR and Mass spectroscopy techniques. Light emitting properties of the compounds have been studied by photoluminescence (PL) and diffuse reflectance (DR) spectra. Photoluminescence spectra of the compounds SB1-SB3 revealed that these molecules emit light from bright yellow to orange red color following exposure to UV light. From diffuse reflectance spectra, the measured optical band energy for SB1-SB3 was found to be 2.14eV, 2.06eV and 2.26eV respectively. The 3D surface view of scanning electron microscope (SEM) of SB1-SB3 have also been studied. This study revealed that Schiff base derivatives of 4-amino benzoic acid analogue molecules become promising material for light emitting devices. Antibacterial study of these compounds by Kirby-Bauer diffusion method revealed the antibacterial activity . This showed these compounds can be used as antibacterial compounds.